Determinasi Rendahnya Literasi Dana Pensiun pada Pekerja: Peran Edukasi dan Digitalisasi dalam Industri Dana Pensiun di Indonesia - Syarifudin Yunus; Farid Nabil Elsyarif (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study uses a quantitative method with an explanatory approach to explore factors contributing to low pension literacy among workers. The sample consisted of 66 workers from both the formal and informal sectors in Jakarta in December 2025. The findings reveal that low pension literacy is not solely due to a lack of knowledge but results from various factors, including low awareness, short-term financial behavior, product complexity, inadequate education, and underutilization of digital tools. There is a mismatch between workers' perceptions and the reality of pension fund behavior. The majority of workers (86%) are unprepared for retirement, and 89% do not have a voluntary pension fund. Despite this, 80% do not rely on workplace pension funds, and 45.5% feel confident they can meet their living expenses in old age, indicating pseudo-awareness they understand the importance of pension funds but have not established one. This reveals a gap between awareness and action regarding pension funds. Improving pension literacy requires an integrated approach that combines transformative education with digitalization to facilitate access and participation. Education must drive behavioral change, while digitalization simplifies processes, enhances accessibility, and broadens financial literacy. The synergy of education, digital technology, and policy support is essential for improving workers' financial readiness for a secure retirement.